Resin composition and product thereof
By using a combination of polyphenylene ether resin containing unsaturated carbon-carbon double bonds and a specific compound, the problem that the existing resin composition cannot meet the high performance requirements is solved, and multiple performance improvements of resin products are achieved, and suitable for the manufacturing of high-performance copper clad plates.
Patent Information
- Application Number
- CN202311125224.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-11
AI Technical Summary
The existing copper clad plate and the resin composition used in preparation cannot meet the characteristics requirements such as high thermal decomposition temperature, low Z-axis thermal expansion rate, low reflow soldering shrinkage rate, high interconnect structure reliability and high flexural modulus.
A resin composition is used which includes 100 parts by weight of a polyphenylene ether resin containing an unsaturated carbon-carbon double bond, 10 to 100 parts by weight of a specific compound (Formula (1)) and 3 to 20 parts by weight of another specific compound (Formula (2)). The composition can self-polymerize or cross-link with other components at high temperatures to form a resin product with excellent mechanical and thermal properties.
It realizes high thermal decomposition temperature, low Z-axis thermal expansion rate, low reflow soldering shrinkage rate, high interconnect structure reliability and high bending modulus of resin products, and meets the high performance characteristics required by copper clad plate in modern electronic equipment.
Smart Images

Figure CN119591808A_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to a resin composition and products made from the same, and in particular to a resin composition applicable to prepregs, resin films, laminates (such as copper foil substrates) and printed circuit boards and products made from the same. Background Art
[0002] As a basic electronic component, printed circuit boards (PCBs) are used in many fields including mobile phones, computers, communication base stations, data centers, automobiles, industrial control, aerospace, etc. Their technical level and reliability have a direct impact on the performance and stability of electronic equipment. With the development of technologies such as 5G and computing power networks, the signal transmission rate and communication frequency have been greatly improved. Copper-clad laminate (CCL, or copper foil substrate) is the substrate material of PCB. It mainly plays the role of interconnection, insulation and support for PCB, and has a great influence on the transmission speed, energy loss, characteristic impedance and other aspects of the signal in the circuit. Therefore, the performance, quality, processability, reliability, stability and other characteristics of PCB depend to a large extent on the performance and quality of copper-clad laminate.
[0003] Advanced PCB packaging technology currently faces problems in process capability, signal integrity, heat dissipation and stress, and puts forward higher requirements on the performance of copper clad laminates, including one or more of higher thermal decomposition temperature, lower Z-axis thermal expansion rate, lower reflow soldering shrinkage rate, higher interconnection structure reliability, higher bending modulus, etc. However, existing copper clad laminates and resin compositions used in their preparation still mainly focus on the general conventional properties of copper clad laminates.
[0004] Therefore, there is an urgent need in the art to develop resin compositions and products thereof that can meet one or more of the aforementioned property requirements. Summary of the invention
[0005] In view of the problems encountered in the prior art, especially the inability of existing materials to meet one or more of the above-mentioned technical problems, the main purpose of the present invention is to provide a resin composition and a product made of the resin composition that can overcome at least one of the above-mentioned technical problems.
[0006] In order to achieve the above object, the present invention discloses a resin composition comprising:
[0007] (A) 100 parts by weight of a polyphenylene ether resin containing unsaturated carbon-carbon double bonds;
[0008] (B) 10 to 100 parts by weight of a compound of formula (1); and
[0009] (C) 3 to 20 parts by weight of a compound of formula (2),
[0010]
[0011] In formula (1), n is an integer from 3 to 6, X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group or a p-vinylphenoxy group;
[0012] In formula (2), each of X', Y' and Z' independently represents an alkyl group having 1 to 4 carbon atoms, a phenyl group, a hydrogen atom or a group containing an unsaturated carbon-carbon double bond.
[0013] For example, in one embodiment, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes any one of vinylbenzyl polyphenylene ether resin, (meth)acryl polyphenylene ether resin and vinyl polyphenylene ether resin or a combination thereof.
[0014] For example, in one embodiment, the compound of formula (1) has at least one o-vinylphenoxy group.
[0015] For example, in one embodiment, the compound of formula (2) has at least one group containing an unsaturated carbon-carbon double bond.
[0016] For example, in one embodiment, in formula (2), at least one of X', Y' and Z' represents a vinyl group, a styryl group, an allyl group or a (meth)acryloyloxy group.
[0017] For example, in one embodiment, the compound of formula (1) includes any one of the compounds of formula (1-1) to formula (1-14) or a combination thereof:
[0018]
[0019]
[0020]
[0021] For example, in one embodiment, the compound of formula (2) includes any one of the compounds of formula (2-1) to formula (2-6) or a combination thereof:
[0022]
[0023]
[0024] For example, in one embodiment, the resin composition further includes 2 to 30 parts by weight of a cross-linking agent containing unsaturated carbon-carbon double bonds, wherein the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane, divinylbenzene, divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate, triallyl cyanurate, vinylbenzocyclobutene, di(vinylbenzyl)ether, trivinylcyclohexane, diallyl bisphenol A, difunctional or higher acrylates, butadiene, decadiene and octadiene, or a combination thereof.
[0025] For example, in one embodiment, the resin composition further includes any one or a combination of polyolefin, benzoxazine resin, epoxy resin, polyester resin, phenol resin, amine curing agent, polyamide, polyimide, styrene maleic anhydride and cyanate ester.
[0026] For example, in one embodiment, the resin composition further comprises any one or a combination of an inorganic filler, a flame retardant different from the compound of formula (1), a hardening accelerator different from the compound of formula (2), an inhibitor, a solvent, a silane coupling agent, a colorant and a toughening agent.
[0027] On the other hand, in order to achieve the above-mentioned object, the present invention also discloses a product made of the above-mentioned resin composition, which includes a prepreg, a resin film, a laminate or a printed circuit board.
[0028] For example, in one embodiment, the aforementioned product has at least one, multiple or all of the following characteristics:
[0029] The thermal decomposition temperature measured according to the method of IPC-TM-6502.4.24.6 is greater than or equal to 430°C;
[0030] The Z-axis thermal expansion ratio measured according to IPC-TM-6502.4.24.5 is less than or equal to 0.89%:
[0031] The Z-axis thermal expansion rate measured according to IPC-TM-6502.4.24.5 is less than or equal to 0.75%;
[0032] The reflow shrinkage measured according to IPC-TM-6502.4.39 is less than or equal to 270ppm;
[0033] The resistance change after 1000 cycles measured according to IPC-TM-6502.6.26 is less than 10%; and
[0034] The flexural modulus measured according to the method of IPC-TM-6502.4.4 is greater than or equal to 22 GPa. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text have the common meanings understood by those skilled in the art for the present invention. In case of conflict, the definitions in this specification shall prevail.
[0036] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0037] The use of "one", "a", "an" or similar expressions to describe the components and technical features of the present invention is merely for the convenience of expression and to provide a general meaning to the scope of the present invention. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.
[0038] As used herein, the terms "comprises," "includes," "has," "contains," or any other similar terms are open-ended transitional phrases, which are intended to cover non-exclusive inclusions. For example, a composition or article comprising a plurality of elements encompasses any one or any one of the listed elements, and is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless expressly stated to the contrary, the term "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, in this article, the terms "comprising", "including", "having", and "containing" should be interpreted as specifically disclosed and simultaneously covering closed conjunctions such as "consisting of", "consisting of", "the remainder of", and conjunctions such as "consisting essentially of", "mainly consisting of", "mainly consisting of", "essentially containing", "essentially consisting of", "essentially consisting of", and "essentially containing".
[0039] Herein, “or a combination thereof” means “or any combination thereof”, covering any combination of more than two of the listed elements; “any one”, “any one”, “any one” means “any one”, “any one”, “any one”. For example, “a composition or its product includes A, B, C or a combination thereof”, when interpreted, covers the following situations: A is true (or exists) and B and C are false (or do not exist), B is true (or exists) and A and C are false (or do not exist), C is true (or exists) and A and B are false (or do not exist), A and B are true (or exist) and C is false (or do not exist), A and C are true (or exist) and B is false (or do not exist), B and C are true (or exist) and A is false (or do not exist), and A, B and C are true (or exist) and B is false (or do not exist), and A, B and C are all true (or exist), and it also covers that the composition or its product contains or does not contain other elements other than A, B and C that are not explicitly listed but are generally inherent to the composition or its product.
[0040] In this article, the terms "and", "with", "and", "as well as" or other similar terms are used to connect parallel sentence components, and there is no distinction between the previous and subsequent components. The meaning of the parallel sentence components does not change after the positions of the parallel sentence components are exchanged in grammatical sense.
[0041] In this article, all features or conditions such as numerical values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclose all possible sub-ranges and individual values (including integers and fractions) within the range, especially integer values. For example, the range description of "1.0 to 8.0", "between 1.0 and 8.0" or "between 1.0 to 8.0" should be deemed to have specifically disclosed all sub-ranges such as 1.0 to 8.0, 1.0 to 7.0, 2.0 to 8.0, 2.0 to 6.0, 3.0 to 6.0, 4.0 to 8.0, 3.0 to 8.0, etc., and should be deemed to cover endpoint values, especially sub-ranges defined by integer values, and should be deemed to have specifically disclosed individual values such as 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, etc. Unless otherwise indicated, the above explanation method applies to all contents of the entire text of the present invention, regardless of whether the scope is broad or not.
[0042] If the quantity, concentration or other numerical value or parameter is expressed as a range, a preferred range (or a better range) or a series of upper and lower limits, it should be understood that all ranges consisting of any pair of the upper limit or preferred value (or a better value) of the range and the lower limit or preferred value (or a better value) of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.
[0043] In this document, numerical values should be understood to have the accuracy of the number of significant digits of the numerical value, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range of 39.50 to 40.49.
[0044] In this article, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that all subgroups or any individual elements in the Markush group or option list can also be used to describe the present invention. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that any combination of subgroups or individual members of all elements in the Markush group or option list can also be used to describe the present invention. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 and / or X2 and / or X3 and Y is Y1 and / or Y2 and / or Y3 has been fully described.
[0045] Unless otherwise specified, in the present invention, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, but not limited thereto. The compound herein is not limited to a single chemical substance when interpreted, but can also be interpreted as the same type of chemical substances with the same composition or the same properties.
[0046] If not otherwise specified, in the present invention, polymer refers to the product formed by the polymerization reaction of monomers, often including many polymer aggregates, each polymer is composed of many simple structural units repeatedly connected by covalent bonds, and the monomer is a compound of the synthetic polymer. Polymers can include homopolymers, copolymers, prepolymers, etc., and are not limited to this. Homopolymers refer to polymers polymerized from a single monomer. Copolymers refer to polymers polymerized from two or more monomers. Copolymers include random copolymers (structures such as -AABABBBAAABBA-), alternating copolymers (structures such as -ABABABAB-), graft copolymers (structures such as -AA(A-BBBB)AA(A-BBBB)AAA-) and block copolymers (structures such as -AAAAA-BBBBBB-AAAAA-), etc. For example, the styrene-butadiene copolymer in the present invention can include styrene-butadiene random copolymers, styrene-butadiene alternating copolymers, styrene-butadiene graft copolymers or styrene-butadiene block copolymers when interpreted. Prepolymer refers to a polymer with a lower molecular weight between the monomer and the final polymer, and the prepolymer contains reactive functional groups that can further undergo polymerization to obtain a fully cross-linked or hardened product with a higher molecular weight. Polymers of course include oligomers, but are not limited to them. Oligomers, also known as low polymers, are polymers composed of 2 to 20 repeating units, usually 2 to 5 repeating units.
[0047] For those skilled in the art, a resin composition containing three compounds A, B and C and an additive (comprising four components in total), and a resin composition containing a prepolymer formed by three compounds A, B and C and an additive (comprising two components in total) are different resin compositions, and the two are completely different in many aspects such as the preparation method, the physical and chemical properties of the compounds themselves, and the properties of their products. For example, the former is to mix A, B, C and additives to form a resin composition, while the latter is to first prepolymerize the mixture including A, B and C under appropriate conditions to form a prepolymer, and then mix the prepolymer with the additive to obtain a resin composition. For example, for those skilled in the art, the above two resin compositions have completely different compositions, and because the function of the prepolymer formed by the three compounds A, B and C in the resin composition is completely different from the function of A, B and C individually or together in the resin composition, the two resin compositions should be regarded as completely different chemical substances with completely different chemical positions. For example, for those skilled in the art, because the above two resin compositions are completely different chemical substances, their products will not have the same properties. For example, a resin composition including a prepolymer formed by three compounds A, B and C and a crosslinking agent, since A, B and C have partially reacted or converted during the prepolymerization reaction to form the prepolymer, when the resin composition is subsequently heated at a high temperature to form a semi-cured state, a partial crosslinking reaction occurs between the prepolymer and the crosslinking agent, rather than A, B and C each undergoing a partial crosslinking reaction with the crosslinking agent. Therefore, the products formed by the two resin compositions will also be completely different and have completely different properties.
[0048] If not otherwise specified, the "resin" in the present invention is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.
[0049] If not otherwise specified, in the present invention, modified products include products after modification of reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after crosslinking of each resin with other resins, products after copolymerization of each resin with other resins, and the like.
[0050] If not otherwise specified, the unsaturated bonds described in the present invention refer to reactive unsaturated bonds, such as but not limited to unsaturated double bonds that can undergo cross-linking reactions with other functional groups, such as but not limited to unsaturated carbon-carbon double bonds that can undergo cross-linking reactions with other functional groups. The unsaturated carbon-carbon double bonds described in the present invention preferably include but are not limited to vinyl, styryl, vinylbenzyl, (meth)acryloyl, allyl or a combination thereof. Vinyl should be interpreted to include vinyl and vinylidene, and (meth)acryloyl should be interpreted to include acryloyl and methacryloyl.
[0051] Unless otherwise specified, the alkyl, alkenyl, and monomers described in the present invention include their various isomers when interpreted. For example, propyl should be interpreted as including n-propyl and isopropyl.
[0052] Unless otherwise specified, in the present invention, parts by weight represent relative parts by weight in the composition, which may be any weight unit, such as but not limited to kilograms, kilograms, grams, pounds, etc. For example, 100 parts by weight of polyphenylene ether resin containing unsaturated carbon-carbon double bonds may represent 100 kilograms of polyphenylene ether resin containing unsaturated carbon-carbon double bonds or 100 pounds of polyphenylene ether resin containing unsaturated carbon-carbon double bonds.
[0053] Unless otherwise specified, in the present invention, wt% represents weight (or mass) percentage.
[0054] It should be understood that the features disclosed in the various embodiments herein may be arbitrarily combined to form the technical solution of the present invention, as long as there is no contradiction in the combination of these features.
[0055] The present invention will be described below with specific embodiments and examples. It should be understood that these specific embodiments and examples are merely exemplary and are not intended to limit the scope of the present invention and its use. The methods, reagents and conditions used in the examples are, unless otherwise stated, methods, reagents and conditions conventional in the art.
[0056] As mentioned above, the present invention mainly discloses a resin composition, comprising the following components:
[0057] (A) 100 parts by weight of a polyphenylene ether resin containing unsaturated carbon-carbon double bonds;
[0058] (B) 10 to 100 parts by weight of the compound of formula (1), for example, 10, 20, 30, 40, 50, 55, 60, 70, 80, 90 or 100 parts by weight, but not limited thereto; and
[0059] (C) 3 to 20 parts by weight of the compound of formula (2), for example, 3, 5, 8, 10, 15 or 20 parts by weight, but not limited thereto;
[0060]
[0061] In formula (1), n is an integer from 3 to 6 (e.g., 3, 4, 5, or 6), and X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group, or a p-vinylphenoxy group. The structures of o-vinylphenoxy, m-vinylphenoxy, and p-vinylphenoxy are as follows, respectively, wherein * represents the position of bonding to the phosphorus atom. For example, in one embodiment, at least one of X and Y is an o-vinylphenoxy group. In other words, in one embodiment, the compound of formula (1) has at least one o-vinylphenoxy group.
[0062] o-Vinylphenoxy:
[0063] m-Vinylphenoxy:
[0064] p-Vinylphenoxy:
[0065] In formula (2), each X', Y' and Z' independently represents an alkyl group having a carbon number of 1 to 4, a phenyl group, a hydrogen atom or a group containing an unsaturated carbon-carbon double bond. For example, in one embodiment, two X's may be the same or different from each other, and independently represent an alkyl group having a carbon number of 1 to 4, a phenyl group, a hydrogen atom or a group containing an unsaturated carbon-carbon double bond. For example, in one embodiment, the compound of formula (2) has at least one group containing an unsaturated carbon-carbon double bond (for example, but not limited to any one or a combination of vinyl, styryl, allyl and (meth)acryloyloxy). For example, in one embodiment, in formula (2), at least one of X', Y' and Z' represents a vinyl, styryl, allyl or (meth)acryloyloxy group.
[0066] For example, in one embodiment, the compound of formula (1) includes any one or a combination of the compounds of formula (1-1) to (1-14) above. For example, in one embodiment, the compound of formula (2) includes any one or a combination of the compounds of formula (2-1) to (2-6) above.
[0067] The polyphenylene ether resin containing unsaturated carbon-carbon double bonds suitable for use in the present invention is not particularly limited, and may be any one or more polyphenylene ether resins containing unsaturated carbon-carbon double bonds suitable for preparing prepregs, resin films, laminates or printed circuit boards, and may be any one or more commercially available products, homemade products or combinations thereof, including, for example, but not limited to, any one or a combination of vinylbenzyl polyphenylene ether resins, (meth)acryl polyphenylene ether resins and vinyl polyphenylene ether resins.
[0068] The polyphenylene ether resin containing unsaturated carbon-carbon double bonds of the present invention has unsaturated carbon-carbon double bonds and a phenylene ether skeleton, wherein the unsaturated carbon-carbon double bonds are reactive functional groups, which can self-polymerize after being heated, and can also undergo free radical polymerization reaction with other unsaturated bond-containing components in the resin composition and finally crosslink and cure. Preferably, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes a polyphenylene ether resin containing unsaturated carbon-carbon double bonds substituted with 2,6-dimethyl on the phenylene ether skeleton, and the methyl groups after substitution form a steric hindrance so that the oxygen atoms on the ether are not easy to generate hydrogen bonds or van der Waals forces and absorb moisture.
[0069] For example, in one embodiment, the polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes, but is not limited to, vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 1200 (e.g., OPE-2st1200, available from Mitsubishi Gas Chemical Co., Ltd.), vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 2200 (e.g., OPE-2st 2200, available from Mitsubishi Gas Chemical Co., Ltd.), vinylbenzyl polyphenylene ether resin having a number average molecular weight of about 2400 to 2800 (e.g., vinylbenzyl bisphenol A polyphenylene ether resin), (meth)acryl polyphenylene ether resin having a number average molecular weight of about 1900 to 2300 (e.g., SA9000, available from Sabic), vinyl polyphenylene ether resin having a number average molecular weight of about 2200 to 3000, or a combination thereof. The vinyl polyphenylene ether resin may include various types of polyphenylene ether resins disclosed in U.S. Patent Application US20160185904A1, all of which are incorporated herein by reference. For example, in one embodiment, the vinylbenzyl polyphenylene ether resin includes, but is not limited to, vinylbenzyl biphenyl polyphenylene ether resin, vinylbenzyl bisphenol A polyphenylene ether resin, or a combination thereof.
[0070] In the present invention, the compound of formula (1) is a cyclic phosphazene compound containing a P=N bond in its structure, wherein n represents the number of P=N bonds, and n is an integer from 3 to 6. In other words, when n is 3, the compound of formula (1) is a cyclic phosphazene having a six-membered ring, and when n is 6, the compound of formula (1) is a cyclic phosphazene having a twelve-membered ring. In addition, the phosphorus atom in the cyclic phosphazene structure of the compound of formula (1) can be substituted by an o-vinylphenoxy group, a m-vinylphenoxy group, or a p-vinylphenoxy group.
[0071] In the present invention, for example, when n is 3, the sum of the numbers of o-vinylphenoxy, m-vinylphenoxy and p-vinylphenoxy groups in the cyclic phosphazene structure of the compound of formula (1) is 6, the number of o-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6, the number of m-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6, and the number of p-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5 or 6. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound of formula (1) is 0, the number of p-vinylphenoxy groups is 6, and the number of m-vinylphenoxy groups is 0. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound of formula (1) is 6, the number of p-vinylphenoxy groups is 0, and the number of m-vinylphenoxy groups is 0. For example, when n is 3, the number of o-vinylphenoxy groups in the cyclic phosphazene structure of the compound of formula (1) is 3, the number of p-vinylphenoxy groups is 2, and the number of m-vinylphenoxy groups is 1. For example, when n is 6, the sum of the numbers of o-vinylphenoxy groups, m-vinylphenoxy groups and p-vinylphenoxy groups in the cyclic phosphazene structure of the compound of formula (1) is 12, the number of o-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, the number of m-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12, and the number of p-vinylphenoxy groups may be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12.
[0072] In the present invention, unless otherwise specified, the pH value of the compound of formula (1) is not particularly limited, and is preferably 5 to 10, such as but not limited to 5, 6, 7, 8, 9 or 10. When the pH value is less than 5 or greater than 10, it will have an adverse effect on the dielectric aging properties of the product. The pH value of the compound can be measured by a measuring instrument known in the art, such as but not limited to a pH meter, or, for example, obtained by titration using an acid-base titration method. For example, in one embodiment, the compound of formula (1) and deionized water with a pH value of 7 are mixed in a weight ratio of 1:10, and the mixed solution is filtered and extracted at room temperature. The pH value of the extract is measured using a pH meter to obtain the pH value of the compound of formula (1). When measured by a pH meter, the pH value of the compound of formula (1) can also be a small value, such as but not limited to 5.5, 6.5 or 7.3, and is not limited thereto.
[0073] In the present invention, unless otherwise specified, the compound of formula (1) can be prepared by various methods known to those skilled in the art.
[0074] For example, the compound of formula (1) can be prepared by the following method:
[0075] Step (1): reacting chlorinated cyclophosphazene with hydroxybenzaldehyde (o-hydroxybenzaldehyde and / or m-hydroxybenzaldehyde and / or p-hydroxybenzaldehyde) to obtain an intermediate product; and
[0076] Step (2): reacting the intermediate product with methyltriphenylphosphonium bromide in the presence of a catalytic base to obtain a compound of formula (1).
[0077] In step (1), an acid binding agent may be further added as needed, and the acid binding agent includes but is not limited to potassium carbonate, triethylamine or a combination thereof.
[0078] In step (1), an organic solvent may be further added as needed, and the organic solvent includes but is not limited to tetrahydrofuran. Unless otherwise specified, the tetrahydrofuran used in the present invention is tetrahydrofuran from which water has been removed (anhydrous tetrahydrofuran).
[0079] In step (1), the chlorinated cyclophosphazene includes but is not limited to hexachlorocyclotriphosphazene, octachlorocyclotetraphosphazene, decachlorocyclopentaphosphazene, dodecachlorocyclohexaphosphazene or a combination thereof. For example, the molar ratio of the chlorinated cyclophosphazene to hydroxybenzaldehyde is 1:6 to 1:12.
[0080] In step (1), for example, the reaction temperature after adding o-hydroxybenzaldehyde, m-hydroxybenzaldehyde or p-hydroxybenzaldehyde is 40 to 70° C., and the reaction time is 24 to 96 hours, preferably 48 to 72 hours.
[0081] In step (2), the catalytic base includes but is not limited to potassium tert-butoxide, sodium methoxide or a combination thereof; for example, the reaction temperature after adding the catalytic base is 25 to 50° C., and the reaction time is 1 to 6 hours, preferably 2 to 3 hours.
[0082] In step (2), an organic solvent may be further added as needed, and the organic solvent includes but is not limited to tetrahydrofuran from which water has been removed.
[0083] In step (2), calcium bromide may be added as needed. The reaction temperature after adding calcium bromide is 25 to 50° C., and the reaction time is 12 to 72 hours, preferably 24 to 48 hours.
[0084] In step (2), for example, the pH value of the reaction system can be adjusted to 3 to 13 by using an aqueous acetic acid solution or an aqueous ammonium chloride solution.
[0085] The compound of formula (2) of the present invention can be obtained commercially, or prepared by various methods known to those skilled in the art. For example, a free radical initiator can be used to induce isopropylbenzene (also known as cumene) to generate the corresponding isopropylbenzene free radical, and the isopropylbenzene free radicals are coupled in pairs to obtain the compound of formula (2-1). The compound of formula (2-2) can be obtained by hydrogenating tetraphenylethylene in the presence of palladium acetate, ethyl acetate, and pinacol borane. The compound of formula (2-3) can be obtained by subjecting benzyl chloride to a Wurtz coupling reaction, a Grignard coupling reaction, or a coupling reaction with an active metal. The compound of formula (2-4) having a styryl group can be obtained by first vinylating 1,1'-bis(4-bromophenyl)ethane with vinylmagnesium bromide, then brominating it with N-bromosuccinimide, and then coupling it with zinc powder. The compound of formula (2-5) having a vinyl group can be obtained by brominating 4-isopropylbenzaldehyde with N-bromosuccinimide, then coupling with zinc powder to obtain 2,3-dimethyl-2,3-bis(4-formylphenyl)butane, and then Wittig reaction with methyltriphenylphosphonium bromide. The compound of formula (2-6) having a (meth)acryloyloxy group can be obtained by coupling acetophenone with titanium tetrachloride, then epoxidizing with benzoic acid peroxide, and then reacting with 10% sulfuric acid solution to generate 1,2-dimethyldiphenylbutanediol, and finally adding methacryloyl chloride to react.
[0086] For example, in one embodiment, the resin composition of the present invention may further include a cross-linking agent containing unsaturated carbon-carbon double bonds. For example, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may contain 2 to 30 parts by weight of the cross-linking agent containing unsaturated carbon-carbon double bonds, preferably 2 to 10 parts by weight of the cross-linking agent containing unsaturated carbon-carbon double bonds.
[0087] The cross-linking agent containing unsaturated carbon-carbon double bonds applicable to the present invention refers to a difunctional or higher molecular compound containing unsaturated carbon-carbon double bonds having a molecular weight less than or equal to 1000, and the molecular weight is preferably between 100 and 900, and more preferably between 100 and 800. For example, the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane (BVPE), divinylbenzene (DVB), divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), vinylbenzocyclobutene (VBCB), di(vinylbenzyl)ether (BVBE), trivinylcyclohexane (TVCH), diallylbisphenol A (DABPA), difunctional or higher acrylate, butadiene, decadiene and octadiene, or a combination thereof.
[0088] The difunctional or higher acrylate includes various difunctional acrylates, trifunctional acrylates or tetrafunctional or higher acrylates known in the art, which can be purchased from Shin-Nakamura Chemical Industry Co., Ltd., Kyoeisha Chemical Co., Ltd., Nippon Kayaku Co., Ltd. or Sartomer Co., Ltd. Specific examples include but are not limited to any one of diallyl isophthalate (DAIP), dioxanediol diacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate or a combination thereof.
[0089] For example, in one embodiment, the resin composition of the present invention further comprises any one of polyolefins, benzoxazine resins, epoxy resins, polyester resins, phenolic resins, amine curing agents, polyamides, polyimides, styrene maleic anhydride, and cyanate esters, or a combination thereof.
[0090] If not otherwise specified, in the resin composition of the present invention, the amount of polyolefin, benzoxazine resin, epoxy resin, polyester resin, phenol resin, polyamide, polyimide, styrene maleic anhydride or cyanate ester relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds is not particularly limited, for example, it can be 1 to 100 parts by weight, such as but not limited to 1 part by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 50 parts by weight or 100 parts by weight. The amount of amine curing agent relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds is also not particularly limited, for example, it can be 1 to 15 parts by weight, such as but not limited to 1 part by weight, 4 parts by weight, 7.5 parts by weight, 12 parts by weight or 15 parts by weight.
[0091] For example, in one embodiment, the resin composition of the present invention may further include polyolefins. The polyolefins suitable for the present invention are not particularly limited, and may be any one or more polyolefins suitable for preparing prepregs, resin films, laminates or printed circuit boards, and may be any one or more commercially available products, homemade products or combinations thereof. For example, the polyolefins suitable for the present invention include but are not limited to diene polymers, monoene polymers, hydrogenated diene polymers or combinations thereof. The diene refers to a hydrocarbon compound containing two unsaturated carbon-carbon double bonds in the molecule, and the monoene refers to a hydrocarbon compound containing one unsaturated carbon-carbon double bond in the molecule. The polyolefins suitable for the present invention include, for example, but are not limited to, polybutadiene, polyisoprene, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-butadiene-divinylbenzene terpolymer, styrene-butadiene-maleic anhydride terpolymer, vinyl-polybutadiene-urea polymer, maleic anhydride-butadiene copolymer, polymethylstyrene, hydrogenated polybutadiene, hydrogenated polyisoprene, hydrogenated styrene-butadiene-divinylbenzene terpolymer, hydrogenated styrene-butadiene-maleic anhydride terpolymer, hydrogenated styrene-butadiene copolymer, hydrogenated styrene-isoprene copolymer, and any one or a combination of multifunctional vinyl aromatic copolymers. For example, if not specifically indicated, the multifunctional vinyl aromatic copolymers used in the present invention may include various types of multifunctional vinyl aromatic copolymers disclosed in U.S. Patent No. US20070129502A1, all of which are incorporated herein by reference.
[0092] In the present invention, for example, the benzoxazine resin may be any type of benzoxazine resin known in the art. Specific examples include, but are not limited to, bisphenol A type benzoxazine resin, bisphenol F type benzoxazine resin, phenolphthalein type benzoxazine resin, dicyclopentadiene type benzoxazine resin, phosphorus-containing benzoxazine resin, diamino type benzoxazine resin, and phenyl, vinyl or allyl modified benzoxazine resin. Suitable commercially available products include, for example, Huntsman sold under the trade names LZ-8270 (phenolphthalein type benzoxazine resin), LZ-8298 (phenolphthalein type benzoxazine resin), LZ-8280 (bisphenol F type benzoxazine resin), LZ-8290 (bisphenol A type benzoxazine resin), or sold under the trade names KZH-5031 (vinyl modified benzoxazine resin), KZH-5032 (phenyl modified benzoxazine resin) by Kolon Industries of Korea. The diaminobenzoxazine resin may be diaminodiphenylmethane benzoxazine resin, diaminodiphenyl ether benzoxazine resin, diaminodiphenyl sulfone benzoxazine resin, diaminodiphenyl sulfide benzoxazine resin or a combination thereof, and is not limited thereto.
[0093] In the present invention, for example, the epoxy resin can be various epoxy resins known in the art. From the perspective of improving the heat resistance of the resin composition, the epoxy resin includes, but is not limited to, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD epoxy resin, novolac epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional novolac epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, p-xylene epoxy resin, naphthalene epoxy resin (e.g., naphthol epoxy resin), benzofuran epoxy resin, isocyanate-modified epoxy resin, any one or a combination thereof. In the present invention, for example, the novolac epoxy resin may be phenol novolac epoxy resin, bisphenol Anovolac epoxy resin, bisphenol F novolac epoxy resin, biphenylnovolac epoxy resin, phenol benzaldehyde epoxy resin, phenol aralkyl novolac epoxy resin or o-cresol novolac epoxy resin. In the present invention, for example, the phosphorus-containing epoxy resin may be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) epoxy resin, DOPO-HQ epoxy resin or a combination thereof.The aforementioned DOPO epoxy resin may be selected from one or more of DOPO-containing phenol novolac epoxy resin, DOPO-containing o-cresol novolac epoxy resin and DOPO-containing bisphenol-A novolac epoxy resin; the aforementioned DOPO-HQ epoxy resin may be selected from one or more of DOPO-HQ-containing phenol novolac epoxy resin, DOPO-HQ-containing o-cresol novolac epoxy resin and DOPO-HQ-containing bisphenol-A novolac epoxy resin, and is not limited thereto.
[0094] In the present invention, for example, the polyester resin may be any polyester resin known in the art. Specific examples include, but are not limited to, polyester resins containing a dicyclopentadiene structure and polyester resins containing a naphthalene ring structure. Specific examples include, but are not limited to, the trade names HPC-8000 or HPC-8150 sold by Dainippon Ink Chemicals.
[0095] In the present invention, for example, the phenolic resin may be any phenolic resin known in the art. Specific examples include, but are not limited to, phenolic resin or phenoxy resin, wherein the phenolic resin includes phenolic resin, o-methylphenolic resin, bisphenol A resin, naphthol resin, biphenyl phenolic resin and dicyclopentadiene phenol resin, but is not limited thereto.
[0096] In the present invention, for example, the amine curing agent may be any amine curing agent known in the art, and specific examples include but are not limited to at least one of diaminodiphenyl sulfone, diaminodiphenylmethane, diaminodiphenyl ether, diaminodiphenyl sulfide and dicyandiamide, or a combination thereof.
[0097] In the present invention, for example, the polyamide may be any of various polyamides known in the art, and specific examples include but are not limited to various commercially available polyamide resin products.
[0098] In the present invention, for example, the polyimide may be any polyimide known in the art, and specific examples include but are not limited to various commercially available polyimide resin products.
[0099] In the present invention, for example, styrene maleic anhydride can be various styrene maleic anhydride known in the art, wherein the ratio of styrene (St) to maleic anhydride (MA) can be 1 / 1, 2 / 1, 3 / 1, 4 / 1, 6 / 1, 8 / 1 or 12 / 1. Specific examples include, but are not limited to, styrene maleic anhydride copolymers sold by Cray Valley under the trade names SMA-1000, SMA-2000, SMA-3000, EF-30, EF-40, EF-60 and EF-80, or styrene maleic anhydride copolymers sold by Polyscope under the trade names C400, C500, C700, C900, etc.
[0100] In the present invention, for example, the cyanate ester may be various cyanate resins known in the art, such as compounds having an Ar-OC=N structure, wherein Ar may be a substituted or unsubstituted aromatic group. From the perspective of improving the heat resistance of the resin composition, specific examples include, but are not limited to, phenolic cyanate resins, bisphenol A cyanate resins, bisphenol F cyanate resins, cyanate resins containing a dicyclopentadiene structure, cyanate resins containing a naphthalene ring structure, phenolphthalein cyanate resins, adamantane cyanate resins, fluorene cyanate resins, or combinations thereof. Among them, the phenolic cyanate resin may be a bisphenol A phenolic cyanate resin, a bisphenol F phenolic cyanate resin, or a combination thereof. For example, the cyanate resin may be a cyanate resin produced by Lonza under the trade names of Primaset PT-15, PT-30S, PT-60S, BA-200, BA-230S, BA-3000S, BTP-2500, BTP-6020S, DT-4000, DT-7000, ULL950S, HTL-300, CE-320, LVT-50, LeCy, etc.
[0101] For example, in one embodiment, the resin composition further includes any one or a combination of an inorganic filler, a flame retardant different from the compound of formula (1), a hardening accelerator different from the compound of formula (2), an inhibitor, a solvent, a silane coupling agent, a colorant and a toughening agent.
[0102] In the present invention, for example, the inorganic filler can be any one or more inorganic fillers suitable for preparing prepregs, resin films, laminates or printed circuit boards, and specific examples thereof include, but are not limited to, silicon dioxide (molten, non-molten, porous or hollow), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, barium titanate, lead titanate, strontium titanate, calcium titanate, magnesium titanate, barium zirconate, lead zirconate, magnesium zirconate, lead zirconate titanate, zinc molybdate, calcium molybdate, magnesium molybdate, ammonium molybdate, zinc molybdate-modified talc, zinc oxide, zirconium oxide, mica, boehmite (AlOOH), calcined talc, talc, silicon nitride, zirconium tungstate, petalite, calcined kaolin or a combination thereof. In addition, the inorganic filler may be spherical (including solid spherical or hollow spherical), fibrous, plate-like, granular, flaky or needle-like, and may be selectively pretreated with a silane coupling agent. For example, in one embodiment, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may further include 10 to 300 parts by weight of the inorganic filler, preferably 50 to 300 parts by weight of the inorganic filler, more preferably 80 to 250 parts by weight of the inorganic filler, but is not limited thereto.
[0103] In the present invention, for example, the flame retardant different from the compound of formula (1) may be any one or more flame retardants suitable for preparing prepregs, resin films, laminates or printed circuit boards, such as but not limited to phosphorus-containing flame retardants or bromine-containing flame retardants. The bromine-containing flame retardant preferably includes decabromodiphenylethane, and the phosphorus-containing flame retardant preferably includes hydroquinone bis-(diphenyl phosphate), bisphenol A bis-(diphenyl phosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (trimethylphosphate, TMP), dimethyl methylphosphonate (dimethyl methy1phosphonate, DMMP), resorcinol bis(dixylenyl phosphate), RDXP (such as PX-200, PX-201, PX-202 and other commercial products)), ammonium polyphosphate (ammonium polyphosphate), melamine polyphosphate, DPPO (diphenylphosphineoxide) and its derivatives (such as bis-DPPO compounds) or resins, melamine cyanurate and tri-hydroxy ethyl isocyanurate, aluminum phosphinate (such as OP-930, OP-935 and other products) or combinations thereof.
[0104] For example, in one embodiment, the flame retardant can be a flame retardant sold by Katayama Chemical Industry Co., Ltd., such as but not limited to V1, V2, V3, V4, V5, V7, S-2, S-4, E-4c, E-7c, E-8g, E-9g, E-10g, E-100, B-3, W-1o, W-2h, W-2o, W-3o, W-4o, OX-1, OX-2, OX-4, OX-6, OX-6+, OX-7, OX-7+, OX-13, BPE-1, BPE-3, HyP-2, API-9, CMPO, ME-20, C-1R, C-1S, C-3R, C-3S or C-11R. The flame retardant of the present invention can include one or more of the above.
[0105] The present invention preferably includes a phosphate flame retardant, for example including but not limited to resorcinol bis(bis-xylyl phosphate) or its polycondensate, a phosphate containing an unsaturated carbon-carbon double bond or a combination thereof.
[0106] The phosphate containing unsaturated carbon-carbon double bonds of the present invention includes the structure shown in P1 below:
[0107]
[0108] Wherein, A is independently an alkyl group having 1 to 3 carbon atoms, and B is a functional group containing an unsaturated carbon-carbon double bond, preferably, B is vinyl, vinylbenzyl, allyl or butadienyl. Specific examples of the phosphate containing an unsaturated carbon-carbon double bond include, but are not limited to, flame retardants sold by Katayama Chemical Industry Co., Ltd. under the trade names of S-2, V2, and B-3.
[0109] For example, in one embodiment, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may further include 1 to 15 parts by weight of a phosphate flame retardant, preferably 2 to 10 parts by weight of a phosphate flame retardant.
[0110] For example, in one embodiment, the weight ratio of the compound of formula (1) to the phosphate flame retardant is between 4:1 and 11:1. For example, but not limited to, the weight ratio of the compound of formula (1) to the phosphate flame retardant is 4:1, 5.5:1, 6.6:1, 7:1, 8:1, 9:1, 10:1 or 11:1. The combination of the compound of formula (1) and the phosphate flame retardant can further improve the dielectric aging properties of the product.
[0111] In the present invention, for example, the hardening accelerator may include a catalyst such as a Lewis base or a Lewis acid. Among them, the Lewis base may include one or more of imidazole, boron trifluoride amine complex, ethyltriphenyl phosphonium chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MZ), triphenylphosphine (TPP) and 4-dimethylaminopyridine (DMAP). The Lewis acid may include a metal salt compound, such as a metal salt compound of manganese, iron, cobalt, nickel, copper, zinc, etc., such as a metal catalyst such as zinc octanoate and cobalt octanoate. The hardening accelerator also includes a hardening initiator different from the compound of formula (2), such as a peroxide that can generate free radicals. The hardening initiator includes, but is not limited to, diisopropylbenzene peroxide (DCP), tert-butyl peroxybenzoate, dibenzoylperoxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B) and bis(tert-butylperoxyisopropyl)benzene or a combination thereof. For example, in one embodiment, the resin composition of the present invention may further include 0.001 to 5 parts by weight of a hardening accelerator, preferably 0.01 to 3.5 parts by weight of a hardening accelerator, and more preferably 0.1 to 2.0 parts by weight of a hardening accelerator, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, but is not limited thereto.
[0112] In the present invention, for example, the inhibitor may include but is not limited to 1,1-diphenyl-2-trinitrophenylhydrazine, methacrylonitrile, nitrogen oxide stable free radicals, triphenylmethyl free radicals, metal ion free radicals, sulfur free radicals (for example, including but not limited to dithioesters), hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol) and 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) or a combination thereof. For example, the above-mentioned nitrogen oxide stable free radicals may include but are not limited to nitrogen oxide free radicals from cyclic hydroxylamines such as 2,2,6,6-tetramethyl-1-oxy-piperidine, 2,2,6,6-substituted-1-piperidinyloxy free radicals or 2,2,5,5-substituted-1-pyrrolidinyloxy free radicals. As a substituent, an alkyl group with a carbon number of less than four, such as a methyl group or an ethyl group, is preferred. Specific nitrogen oxide free radical compounds are not limited, and examples include but are not limited to 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetraethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetramethyl-4-oxo-1-piperidinyloxy free radicals, 2,2,5,5-tetramethyl-1-pyrrolidinyloxy free radicals, 1,1,3,3-tetramethyl-2-isoindolinyloxy free radicals, N,N-di-tert-butylamineoxy free radicals, etc. Stable free radicals such as galvinoxyl free radicals can also be used to replace nitrogen oxide free radicals. The inhibitor suitable for the resin composition of the present invention can also be a product derived from the hydrogen atom or atomic group in the inhibitor being replaced by other atoms or atomic groups. For example, the hydrogen atom in the inhibitor is replaced by an atomic group such as amino, hydroxyl, ketocarbonyl and the like. For example, in one embodiment, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may further include 0.001 to 20 parts by weight of a polymerization inhibitor, preferably 0.001 to 10 parts by weight of a polymerization inhibitor, but is not limited thereto.
[0113] In the present invention, for example, the solvent can be any solvent suitable for dissolving the resin composition of the present invention, including but not limited to: methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, nitrogen methyl pyrrolidone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether acetate and other solvents or mixed solvents thereof. The amount of solvent added is to be able to completely dissolve the resin and adjust to a specific total solid content of the resin composition. For example, in one embodiment, the amount of solvent added is added to adjust the total solid content of the resin composition to 50% to 85%, but is not limited thereto.
[0114] In the present invention, for example, the silane coupling agent may include a silane compound (silane, for example, including but not limited to a siloxane compound), which may be further divided into an aminosilane compound, an epoxysilane compound, a vinylsilane compound, a hydroxysilane compound, an isocyanatesilane compound, a methacryloxysilane compound, and an acryloxysilane compound according to the type of functional group. For example, in one embodiment, the resin composition of the present invention may further include 0.001 to 20 parts by weight of a silane coupling agent, preferably 0.01 to 10 parts by weight of a silane coupling agent, relative to 100 parts by weight of a polyphenylene ether resin containing unsaturated carbon-carbon double bonds, but is not limited thereto.
[0115] In the present invention, for example, the coloring agent may include but is not limited to a dye or a pigment. For example, in one embodiment, relative to 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may further include 0.001 to 10 parts by weight of the coloring agent, preferably 0.01 to 5 parts by weight of the coloring agent, but is not limited thereto.
[0116] In the present invention, the main function of adding a toughening agent is to improve the toughness of the resin composition. For example, the toughening agent suitable for the present invention may include, but is not limited to, carboxyl-terminated butadiene acrylonitrile rubber (CTBN), core-shell rubber, ethylene-propylene rubber and other compounds or combinations thereof. For example, in one embodiment, relative to 100 parts by weight of a polyphenylene ether resin containing unsaturated carbon-carbon double bonds, the resin composition of the present invention may further include 1 to 20 parts by weight of a toughening agent, preferably 3 to 10 parts by weight of a toughening agent, but is not limited thereto.
[0117] The present invention also provides a product made of the resin composition, such as a component suitable for various electronic products, including but not limited to a prepreg, a resin film, a laminate or a printed circuit board.
[0118] For example, the resin composition of the present invention can be made into a semi-cured sheet, which includes a reinforcing material and a layered object disposed on the reinforcing material. The layered object is obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the semi-cured sheet is between 120°C and 180°C, preferably between 120°C and 160°C. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be various glass fiber cloths that can be used for printed circuit boards, such as E-type glass cloth, D-type glass cloth, S-type glass cloth, T-type glass cloth, L-type glass cloth, Q-type glass cloth or QL-type glass cloth (a glass cloth of a mixed structure made of Q glass and L glass); the types of glass fibers include yarns and rovings, etc., and the forms include open fiber or unopen fiber, and the end face shape includes a circular or flat shape. The aforementioned non-woven fabric preferably includes a liquid crystal resin non-woven fabric, such as a polyester non-woven fabric, a polyurethane non-woven fabric, etc., and is not limited thereto. The aforementioned fabric may also include a liquid crystal resin fabric, such as a polyester fabric or a polyurethane fabric, etc., and is not limited thereto. This reinforcing material can increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material can also be selectively pretreated with a silane coupling agent. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.
[0119] For example, the resin composition of the present invention can be made into a resin film, which is obtained by semi-curing the aforementioned resin composition after baking and heating. The resin composition can be selectively coated on a liquid crystal resin film, a polytetrafluoroethylene film, a polyethylene terephthalate film (PET film), a polyimide film (PT film), a copper foil or a copper foil with adhesive, and then semi-cured after baking and heating, so that the resin composition forms a resin film.
[0120] For example, the resin composition described in the present invention can be made into various laminates, which include at least two metal foils and at least one insulating layer, wherein the insulating layer is disposed between the two metal foils, and the insulating layer can be formed by curing the aforementioned resin composition under high temperature and high pressure (C-stage), and the applicable curing temperature is, for example, between 190°C and 220°C, preferably between 200°C and 210°C, and the curing time is 90 to 180 minutes, preferably 120 to 150 minutes. The aforementioned insulating layer can be obtained by curing the aforementioned semi-cured sheet or resin film. The material of the aforementioned metal foil can be copper, aluminum, nickel, platinum, silver, gold or their alloys, such as copper foil. In a preferred embodiment, the laminate is a copper foil substrate.
[0121] In one embodiment, the aforementioned laminate can be further processed into a printed circuit board after circuit processing. One of the methods for making the printed circuit board of the present invention can be to use a double-sided copper-clad laminate (such as product EM-827, which can be purchased from Taiwan Optoelectronics Materials) with a thickness of 28 mils and 1 ounce of HTE (High Temperature Elongation) copper foil, and electroplating after drilling to form electrical conduction between the upper copper foil and the bottom copper foil. The upper copper foil and the bottom copper foil are then etched to form an inner layer circuit. The inner layer circuit is then browned and roughened to form a concave-convex structure on the surface to increase the roughness. Then, the copper foil, the aforementioned prepreg, the aforementioned inner layer circuit board, the aforementioned prepreg, and the copper foil are stacked in sequence, and then a vacuum laminating device is used to heat for 90 to 180 minutes at a temperature of 190°C to 220°C to cure the insulating layer material of the prepreg. Next, various circuit board processing techniques known in the art such as blackening, drilling, and copper plating are performed on the copper foil on the outermost surface to obtain a printed circuit board.
[0122] For example, in one embodiment, the resin composition disclosed in the present invention and various products prepared therefrom preferably have one, more or all of the following characteristics:
[0123] The thermal decomposition temperature of the article measured according to the method of IPC-TM-650 2.4.24.6 is greater than or equal to 430° C., for example, between 430° C. and 490° C.;
[0124] The article has a Z-axis thermal expansion coefficient measured according to IPC-TM-650 2.4.24.5 of less than or equal to 0.89%, such as less than or equal to 0.75%, or such as between 0.50% and 0.89%;
[0125] The reflow shrinkage of the product measured according to the method of IPC-TM-650 2.4.39 is less than or equal to 270 ppm, for example, between 140 ppm and 270 ppm;
[0126] The resistance value change rate of the product after 1000 cycles measured according to the method of IPC-TM-650 2.6.26 is less than 10%; and
[0127] The flexural modulus of the article measured according to the method of IPC-TM-650 2.4.4 is greater than or equal to 22 GPa, for example, between 22.1 GPa and 26.1 GPa.
[0128] The resin compositions of the embodiments of the present invention and the comparative examples of the present invention were prepared using various raw materials from the following sources and in the amounts shown in Tables 1 to 5, and were further made into various test samples.
[0129] The chemical raw materials used in the embodiments of the present invention and the comparative examples are as follows:
[0130] SA9000: (meth)acryl polyphenylene ether resin, available from Sabic.
[0131] OPE-2st 2200: vinyl benzyl polyphenylene ether resin, purchased from Mitsubishi Gas Chemical.
[0132] OPE-2st 1200: vinyl benzyl polyphenylene ether resin, purchased from Mitsubishi Gas Chemical.
[0133] The compound of formula (1-1) was synthesized by ourselves, as described in detail below.
[0134] The compound of formula (1-2) was synthesized by ourselves, as described in detail below.
[0135] Compound of formula (1-4): synthesized by ourselves, as described in detail below.
[0136] Compounds of formula (1-9): synthesized by ourselves, as described in detail below.
[0137] Compound of formula (2-1): 2,3-dimethyl-2,3-diphenylbutane, purchased from Wuxi Zhufeng Chemical.
[0138] Compound of formula (2-2): 1,1,2,2-tetraphenylethane, purchased from Wuxi Zhufeng Chemical.
[0139] Compound of formula (2-3): 1,2-di-p-tolylethane, purchased from Wuxi Zhufeng Chemical.
[0140] The compound of formula (2-4) was synthesized by ourselves, as described in detail below.
[0141] The compound of formula (2-5) was synthesized by ourselves, as described in detail below.
[0142] Compound of formula (2-6): synthesized by ourselves, as described in detail below.
[0143] SPV-100: Allyl cyclophosphazene, purchased from Otsuka Chemical.
[0144] Di-DOPO: di-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, the structure is as follows.
[0145]
[0146] PX-200: Resorcinol bis(di-xylyl phosphate), purchased from Daihachi Chemical Co., Ltd., Japan.
[0147] S-2: diethyl p-vinylbenzyl phosphate, purchased from Katayama Chemical Co., Ltd.
[0148] DCP: dicumyl peroxide, purchased from NOF Corporation.
[0149] 25B: 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, purchased from NOF Corporation.
[0150] 2E4MZ: 2-ethyl-4-methylimidazole, purchased from Chin Yu Enterprise Co., Ltd.
[0151] DVB: divinylbenzene, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0152] BVPE: bis(vinylphenyl)ethane, purchased from Linchuan Chemical.
[0153] TAIC: triallyl isocyanurate, purchased from Chin Yu Enterprise Co., Ltd.
[0154] SC-2500-SVJ: spherical silica, purchased from Admatechs.
[0155] Toluene: purchased from Sinopec. The toluene content is expressed as "appropriate amount", which means that the toluene content is adjusted to a solid content of 60% to 68% (S / C = 60% to 68%) of the resin composition.
[0156] The composition and property test results of the resin compositions of the embodiments and comparative examples of the present invention are shown in the following table:
[0157] [Table 1] Composition and property test results of the resin composition of the embodiment (unit: weight parts)
[0158]
[0159] [Table 2] Composition and property test results of the resin composition of the embodiment (unit: weight parts)
[0160]
[0161]
[0162] [Table 3] Composition and property test results of the resin composition of the embodiment (unit: weight parts)
[0163]
[0164]
[0165] [Table 4] Composition and property test results of the resin composition of the comparative example (unit: parts by weight)
[0166]
[0167]
[0168] [Table 5] Composition and property test results of the resin composition of the comparative example (unit: parts by weight)
[0169]
[0170]
[0171] For example, in one embodiment, the compound of formula (1) is prepared by the following process.
[0172] Preparation Example 1: Self-made compound of formula (1-1):
[0173] Add 31.2 g of NaH and 400 ml of anhydrous tetrahydrofuran to a 1-liter three-necked flask, introduce nitrogen, stir and heat to 50°C, dissolve 75.2 g of p-hydroxybenzaldehyde in 200 ml of anhydrous tetrahydrofuran, slowly add dropwise to the three-necked flask, continue to react for 4 hours after the addition is complete, then dissolve 34.7 g of hexachlorocyclotriphosphazene in 200 ml of anhydrous tetrahydrofuran, add to the three-necked flask, heat to 65°C, react for 48 hours, filter, and rotary evaporate to obtain an intermediate product.
[0174] At room temperature, 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, the liquids were separated, and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), and the product was separated and purified by silica gel chromatography. The obtained product is marked as the compound of formula (1-1), and its pH value is 8. The structural formula is as follows.
[0175]
[0176] Preparation Example 2: Self-made compound of formula (1-2):
[0177] Add 31.2 g of NaH and 400 ml of anhydrous tetrahydrofuran to a 1-liter three-necked flask, introduce nitrogen, stir and heat to 50°C, dissolve 75.2 g of o-hydroxybenzaldehyde in 200 ml of anhydrous tetrahydrofuran, slowly dropwise add to the three-necked flask, continue to react for 4 hours after the addition is complete, then dissolve 34.7 g of hexachlorocyclotriphosphazene in 200 ml of anhydrous tetrahydrofuran, add to the three-necked flask, heat to 65°C, react for 48 hours, filter, and rotary evaporate to obtain an intermediate product.
[0178] At room temperature, 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 3 hours, 600 g of calcium bromide was added, and the reaction was stirred for 30 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column. The obtained product was marked as a compound of formula (1-2), and its pH value was 8. The structural formula is as follows.
[0179]
[0180] Preparation Example 3: Self-made compound of formula (1-3):
[0181] At room temperature, 100 g of hexachlorocyclotriphosphazene, 270 g of potassium carbonate and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 37 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 40°C and the reaction was continued for 72 hours. Then, 366 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 48 hours, and the intermediate product was obtained by filtering and rotary evaporation.
[0182] At room temperature, 315 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 4 to 5, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-3), whose pH value is 5 and the structural formula is as follows.
[0183]
[0184] Preparation Example 4: Self-made compound of formula (1-4):
[0185] At room temperature, 100 g of hexachlorocyclotriphosphazene, 198 g of triethylamine and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 110 g of o-hydroxybenzaldehyde was slowly dropped into the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 50°C and the reaction was continued for 64 hours. Then, 220 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 60 hours. The mixture was filtered and rotary evaporated to obtain an intermediate product.
[0186] At room temperature, 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-4), whose pH value is 8 and the structural formula is as follows.
[0187]
[0188]
[0189] Preparation Example 5: Self-made compound of formula (1-5):
[0190] At room temperature, 100 g of hexachlorocyclotriphosphazene, 270 g of potassium carbonate and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 183 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 60°C and the reaction was continued for 56 hours. Then, 73 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 72 hours, and the intermediate product was obtained by filtration and rotary evaporation.
[0191] At room temperature, 400 g of dehydrated methyltriphenylphosphonium bromide and 550 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 48 g of sodium methoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An aqueous ammonium chloride solution was added to adjust the pH value to 9 to 10, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as the mobile phase (cyclohexane: ethyl acetate = 500: 1 to 10: 1), and the product was separated and purified by silica gel chromatography to obtain a product marked as the compound of formula (1-5), whose pH value is 10 and the structural formula is as follows.
[0192]
[0193] Preparation Example 6: Self-made compound of formula (1-6):
[0194] At room temperature, 134 g of octachlorocyclotetraphosphazene, 359 g of potassium carbonate and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 147 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 70°C and the reaction was continued for 48 hours. Then, 294 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 48 hours, and the intermediate product was obtained by filtering and rotary evaporation.
[0195] At room temperature, 315 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of a tetrahydrofuran solution of an intermediate product having a dehydrated concentration of 0.17 g / ml were added to a three-necked flask, and the mixture was stirred. 135 g of potassium tert-butoxide was slowly added. After reacting for 3 hours, 700 g of calcium bromide was added. The mixture was stirred and reacted for 48 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8. The tetrahydrofuran in the system was removed by rotary evaporation. Dichloroethane was added, the phases were separated, and the oil phase was collected. After the dichloroethane was removed by rotary evaporation, a mixed solution of cyclohexane and dichloroethane was used as a mobile phase (cyclohexane: dichloroethane = 500: 1 to 10: 1). The mixture was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-6). The pH value of the compound is 8 and the structural formula is as follows.
[0196]
[0197] Preparation Example 7: Self-made compound of formula (1-7):
[0198] At room temperature, 168 g of decachlorocyclopentaphosphazene, 442 g of potassium carbonate and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 183 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 70°C and the reaction was continued for 48 hours. Then, 366 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 48 hours, and the intermediate product was obtained by filtering and rotary evaporation.
[0199] At room temperature, 315 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 170 g of potassium tert-butoxide was slowly added, and after reacting for 3 hours, 600 g of calcium bromide was added, and the reaction was stirred for 36 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-7), whose pH value is 8 and the structural formula is as follows.
[0200]
[0201] Preparation Example 8: Self-made compound of formula (1-8):
[0202] At room temperature, 201 g of dodecachlorocyclohexaphosphazene, 525 g of potassium carbonate and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 220 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 70°C and the reaction was continued for 48 hours. Then, 440 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask, the reaction was continued for 60 hours, and the intermediate product was obtained by filtration and rotary evaporation.
[0203] At room temperature, 315 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 3 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-8), whose pH value is 8 and the structural formula is as follows.
[0204]
[0205] Preparation Example 9: Self-made compound of formula (1-9):
[0206] At room temperature, 100 g of hexachlorocyclotriphosphazene, 198 g of triethylamine and 400 ml of tetrahydrofuran were added to a three-necked flask. After sufficient dissolution, the three-necked flask was moved to an ice-water bath. 110 g of o-hydroxybenzaldehyde was slowly dropped into the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 50°C and the reaction was continued for 64 hours. Then, 220 ml of a tetrahydrofuran solution of m-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask. The reaction was continued for 60 hours. The mixture was filtered and the intermediate product was obtained by rotary evaporation.
[0207] At room temperature, 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-9), whose pH value is 8 and the structural formula is as follows.
[0208]
[0209] Preparation Example 10: Self-prepared compound of formula (1-10):
[0210] At room temperature, 100 g of hexachlorocyclotriphosphazene, 198 g of triethylamine and 400 ml of tetrahydrofuran were added to a three-necked flask. After fully dissolved, the three-necked flask was moved to an ice-water bath. 73 g of o-hydroxybenzaldehyde was slowly added dropwise to the three-necked flask. After 2 hours of dropwise addition, the temperature was raised to 50° C. and the reaction was continued for 64 hours. Then, 146 ml of a tetrahydrofuran solution of p-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask and the reaction was continued for 60 hours. Then, 146 ml of m-hydroxybenzaldehyde with a concentration of 0.5 g / ml was added dropwise to the three-necked flask and the reaction was continued for 60 hours. The reaction was continued, and the intermediate product was filtered and rotary evaporated.
[0211] At room temperature, 350 g of dehydrated methyltriphenylphosphonium bromide and 500 ml of dehydrated tetrahydrofuran solution of the intermediate product with a concentration of 0.17 g / ml were added to a three-necked flask, stirred, 100 g of potassium tert-butoxide was slowly added, and after reacting for 2 hours, 600 g of calcium bromide was added, and the reaction was stirred for 24 hours. An acetic acid aqueous solution was added to adjust the pH value to 7 to 8, and tetrahydrofuran in the system was removed by rotary evaporation. Ethyl acetate was added, and the liquids were separated and the oil phase was collected. After the ethyl acetate was removed by rotary evaporation, a mixed solution of cyclohexane and ethyl acetate was used as a mobile phase (cyclohexane: ethyl acetate = 500: 1-10: 1), and the product was separated and purified by a silica gel chromatography column to obtain a product marked as a compound of formula (1-10), whose pH value is 8 and the structural formula is as follows.
[0212]
[0213] For example, in one embodiment, the compound of formula (2) is prepared by the following process.
[0214] Preparation Example 11: Self-made compound of formula (2-4):
[0215] In a three-necked flask, 1 mol of 1,1′-bis(4-bromophenyl)ethane, 1.2 mol of tetrahydrofuran solution of vinylmagnesium bromide and 0.05 mol of palladium dichloride were sequentially added under nitrogen protection. After reflux for 24 hours, saturated aqueous ammonium chloride solution was added to quench, and the mixture was extracted with dichloromethane solution. After combining the organic phases, the solvent was evaporated to obtain a crude product, and 0.9 mol of 1,1′-bis(4-vinylphenyl)ethane was separated by column chromatography.
[0216] In a three-necked flask, 0.8 mol of 1,1′-bis(4-vinylphenyl)ethane, 1.6 mol of N-bromosuccinimide, 0.05 mol of dibenzoyl peroxide and an appropriate amount of carbon tetrachloride were added in sequence, and the reaction was refluxed for 12 hours. The reaction solution was washed three times with sodium thiosulfate solution, and the solvent was evaporated to obtain a dry powder solid. After recrystallization from acetone, 1,1′-bis(4-vinylphenyl)-1-bromoethane was obtained.
[0217] 0.5 mol of 1,1'-bis(4-vinylphenyl)-1-bromoethane and 1 mol of silver-activated zinc powder were added to the reaction flask in sequence, and the reaction was allowed to react for 2 hours. After cooling to room temperature, the reaction was quenched with saturated ammonium chloride, filtered to remove unreacted zinc powder, and 2,3-tetra(4-vinylphenyl)butane was separated by column chromatography and marked as the compound of formula (2-4), with the structural formula as follows.
[0218]
[0219] Preparation Example 12: Self-prepared compound of formula (2-5):
[0220] 0.01 mol of 4-isopropylbenzaldehyde, 0.02 mol of N-bromosuccinimide, 0.05 mol of dibenzoyl peroxide and 10 ml of carbon tetrachloride were added to the reaction flask, and the mixture was refluxed for 12 hours. The product was concentrated and purified by chromatography to obtain 2-bromo-2-4-formylphenylpropane.
[0221] Add 0.01 mol of 2-bromo-2-4-formaldehyde phenyl propane and 0.02 mol of silver-activated zinc powder into a reaction flask, react for 2 hours, filter to remove unreacted zinc powder, and purify with a chromatography column to obtain 2,3-dimethyl-2,3-bis(4-formaldehyde phenyl)butane.
[0222] Anhydrous calcium chloride was added to tetrahydrofuran, and the mixture was allowed to stand overnight to remove water. 0.01 mol of 2,3-dimethyl-2,3-bis(4-formylphenyl)butane, 0.015 mol of methyltriphenylphosphonium bromide and 15 ml of tetrahydrofuran were added to a four-necked flask. 0.015 mol of potassium tert-butoxide was slowly added under ice-water bath conditions. The mixture was reacted at room temperature for 2 hours. A saturated aqueous solution of ammonium chloride was added to inactivate the phosphorus ylide. Excess salt was filtered out. 0.03 mol of calcium bromide was added to the filtrate, and the mixture was stirred for 18 hours and filtered. The crude product was purified by chromatography to obtain 2,3-dimethyl-2,3-bis(4-vinylphenyl)butane, which was marked as the compound of formula (2-5) with the following structural formula.
[0223]
[0224] Preparation Example 13: Self-prepared compound of formula (2-6):
[0225] 0.6 mol of acetophenone in tetrahydrofuran solution was added to a three-necked flask under nitrogen protection, and 1.8 mol of titanium tetrachloride was added dropwise in an ice bath. After the addition was complete, the mixture was stirred at room temperature for 10 minutes and refluxed for 12 hours. After the reaction was completed, the mixture was cooled to room temperature by monitoring by TLC, potassium carbonate solution was added to precipitate, and the filter cake was obtained by filtration, and then extracted with dichloromethane. Finally, the solvent was evaporated to obtain 0.25 mol of 1,2-dimethylphenylethylene.
[0226] In a three-necked flask, 0.24 mol of dichloromethane solution of benzoic acid peroxide was added dropwise to 0.2 mol of dichloromethane solution of 1,2-dimethylstilbene in an ice bath. After the addition was complete, the mixture was reacted at room temperature for 24 hours. The reaction was completed as detected by TLC. The organic phase was extracted with sodium thiosulfate solution and sodium bicarbonate solution in turn, and the solvent was evaporated to obtain a dry powder solid. After recrystallization from acetone, 0.16 mol of 1,2-dimethylstilbene epoxide was obtained.
[0227] In a three-necked flask, add 0.15 mol of tetrahydrofuran solution of 1,2-dimethylphenylethylene epoxide, add 0.6 mol of 10% sulfuric acid solution at room temperature, and reflux for 8 hours to complete the reaction. Pour the reaction solution into 5 liters of cold water to precipitate solids, filter to obtain a filter cake, and recrystallize from ethanol to obtain 0.14 mol of 1,2-dimethyldiphenylbutanediol.
[0228] 0.1 mol of 1,2-dimethyldiphenylbutanediol, 0.15 mol of methacryloyl chloride and toluene were added in sequence into a three-necked flask equipped with a water separator, and 0.01 mol of concentrated sulfuric acid was slowly added. After refluxing for 24 hours, the reaction solution was neutralized with 10% sodium hydroxide solution, extracted with ethyl acetate, washed with saturated brine, and the solvent was evaporated to obtain a dry powder solid. After recrystallization from isopropanol / n-hexane, 0.08 mol of 2,3-diphenylbutane-2,3-diylbis(2-methylacrylate) was obtained, marked as the compound of formula (2-6), with the structural formula as follows.
[0229]
[0230] The characteristic tests of the embodiments and comparative examples of the present invention are performed by making the objects to be tested (also called test specimens or samples) according to the following method and then performing the tests according to specific test conditions.
[0231] (1) Precured sheet: The resin compositions of the examples or comparative examples are respectively selected and uniformly mixed to form a varnish, which is then injected into an impregnation tank. A glass fiber cloth (e.g., L-glass fiber cloth with a specification of 2116 or L-glass fiber cloth with a specification of 1080, both purchased from Asahi Co., Ltd.) is then immersed in the impregnation tank to allow the resin composition to adhere to the glass fiber cloth. The varnish is then heated at 150° C. to 170° C. to a semi-cured state (B-Stage), thereby obtaining a precured sheet.
[0232] (2) Copper foil substrate (8-ply, 8 prepregs pressed together): 2 ultra-low surface roughness (HVLP) copper foils with a thickness of 18 microns and 8 2116 L-glass fiber cloths were prepared to impregnate the prepregs prepared by the samples to be tested (each group of examples or comparative examples), and the resin content of each prepreg was about 53%. One HVLP copper foil, eight prepregs, and one HVLP copper foil were stacked in this order, and pressed together under vacuum conditions, a pressure of 420 psi, and 200° C. for 2 hours to form a copper foil substrate, wherein the 8 stacked prepregs were cured to form an insulating layer between the two copper foils, and the resin content of the insulating layer was about 53%.
[0233] (3) Ten-layer board: Prepare EM-LX copper-containing substrate (available from Taiwan Optoelectronics Materials Co., Ltd., with a thickness of 3 mils, using 1078E-glass fiber cloth and 18-micron thick HTE copper foil), and make circuits on the surface copper foil of the copper-containing substrate (such as known exposure, lithography, and etching processes, which are not repeated here) to make a core board. After the core board is made, prepare a second prepreg (made from the resin composition of each group of embodiments and comparative examples, using 1027L-glass fiber cloth), overlap a second prepreg on both sides of the core board, and overlap another 18-micron thick HTE copper foil on the other side of the second prepreg relative to the core board, and press and cure for 2 hours under vacuum conditions, high temperature (200°C) and high pressure (360psi) to complete the first pressing. Then perform a drilling process to make alignment holes, and then perform an in-hole metallization process and a circuit process to complete the first layer-increasing step, thereby forming a four-layer board. Repeat the above-mentioned layer-building steps to form a six-layer board (second layer-building, second pressing), an eight-layer board (third layer-building, third pressing), and finally a ten-layer board (fourth layer-building, fourth pressing).
[0234] (4) Copper-free substrate (8-ply, formed by pressing together 8 prepregs): The above copper foil substrate (8-ply) is etched to remove 2 copper foils to obtain a copper-free substrate (8-ply). The copper-free substrate is formed by pressing together 8 prepregs. The resin content of the copper-free substrate is about 53%.
[0235] The test methods and characteristic analysis items of the samples to be tested are as follows:
[0236] 1. Thermal decomposition temperature (Td)
[0237] The aforementioned copper-free substrate was used to prepare the sample to be tested (25 mg), and the TGA test method of IPC-TM-650 2.4.24.6 was used for measurement, with a heating rate of 10°C / min, an end temperature of 600°C, and a temperature at which the thermal weight loss was 5% as the thermal decomposition temperature. When the thermal decomposition temperature was greater than or equal to 400°C, and the difference in thermal decomposition temperature was greater than or equal to 1%, it indicated that there was a significant difference between different samples (there was a significant technical difficulty).
[0238] 2. Percent of thermal expansion, z-axis, Z-PTE
[0239] The aforementioned copper-free substrate was used to prepare the test samples, and the thermal mechanical analysis (TMA) was performed according to the method of IPC-TM-650 2.4.24.5. The temperature was raised from 50°C to 260°C at a heating rate of 10°C / min, and the Z-axis thermal expansion coefficient (in %) of each test sample within the temperature range of 50°C to 260°C was measured. When the Z-axis thermal expansion coefficient is less than or equal to 1%, the difference in the Z-axis thermal expansion coefficient is greater than or equal to 2%, which means that there are significant differences between different samples (there is a significant technical difficulty).
[0240] 3. Reflow shrinkage-stretch rate
[0241] The above-mentioned ten-layer board was used to make the sample to be tested (6 inches long and 3 inches wide), and the distance between the four corner targets of each sample was measured by a 3D measuring instrument as L1. After each sample was reflowed at 260°C for 3 times, the distance between the four corner targets of each sample was measured again by a 3D measuring instrument as L2, and then the reflow shrinkage rate was calculated by referring to the method of IPC-TM-6502.4.39 = (L1-L2) / L1 (in ppm). When the difference in the reflow shrinkage rate is greater than or equal to 3%, it means that there is a significant difference between different samples (there is a significant technical difficulty).
[0242] 4. Interconnect stress test (IST)
[0243] Interconnect stress test (IST), also known as DC induction thermal cycle test, is a rapid method for thermal stress testing of finished PCBs. It is used to evaluate the reliability of the interconnect structure of finished PCBs.
[0244] According to the following structural description, the resin composition in the embodiment or comparative example is made into a 26-layer PCB board sample, dried, and then the PCB board sample is tested for the resistance value change rate after 1000 cycles of room temperature-150°C-room temperature (heating for 3 minutes, cooling for 2 minutes, and one cycle for every 5 minutes) using the interconnection stress test equipment model IST-HC produced by PWB Company, with reference to the method of IPC-TM-6502.6.26. If the resistance value change rate is greater than or equal to 10%, it means that the reliability of the interconnection structure is unqualified, marked as "NG"; conversely, if the resistance value change rate is less than 10%, it means that the reliability of the interconnection structure is qualified, marked as "pass".
[0245] The structure design of the 26-layer PCB sample for interconnect stress testing is as follows:
[0246] L1 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0247] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0248] L2 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0249] 1 sheet of 3 mil 1086 L-glass cloth core board
[0250] L3 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0251] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0252] L4 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0253] 1 sheet of 3 mil 1086 L-glass cloth core board
[0254] L5 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0255] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0256] L6 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0257] 2 sheets of 1037 L-glass fiber cloth with a total thickness of 3.5 mils core board
[0258] L7 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0259] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0260] L8 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0261] 2 sheets of 1037 L-glass fiber cloth with a total thickness of 3.5 mils core board
[0262] L9 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0263] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0264] L10 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0265] 2 sheets of 4 mil total thickness 106 L-glass fiber cloth core board (enclosed area)
[0266] L11 1 sheet of 2oz thick ultra-low surface roughness (HVLP) copper foil
[0267] 2 sheets of 1080 L-glass cloth with 71% resin content prepreg
[0268] L12 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0269] 2 sheets of 4 mil total thickness 106 L-glass fiber cloth core board
[0270] L13 1 sheet of 2oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0271] 3 sheets of 1080 L-glass fiber cloth with 71% resin content prepreg
[0272] L14 1 sheet of 2oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0273] 2 sheets of 4 mil total thickness 106 L-glass fiber cloth core board
[0274] L15 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0275] 2 sheets of 1080 L-glass cloth with 71% resin content prepreg
[0276] L16 1 sheet of 2oz thick ultra-low surface roughness (HVLP) copper foil
[0277] 2 sheets of 4 mil total thickness 106 L-glass fiber cloth core board (enclosed area)
[0278] L17 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0279] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0280] L18 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0281] 2 sheets of 1037 L-glass fiber cloth with a total thickness of 3.5 mils core board
[0282] L19 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0283] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0284] L20 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuits)
[0285] 2 sheets of 1037 L-glass fiber cloth with a total thickness of 3.5 mils core board
[0286] L21 1 sheet of 1oz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0287] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0288] L22 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0289] 1 sheet of 3 mil 1086 L-glass cloth core board
[0290] L23 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0291] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0292] L24 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0293] 1 sheet of 3 mil 1086 L-glass cloth core board
[0294] L25 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0295] 2 sheets of 106 L-glass fiber cloth with 75% resin content prepreg
[0296] L26 1 Hoz thick ultra-low surface roughness (HVLP) copper foil (made into circuit)
[0297] Among them, 1oz copper foil corresponds to a thickness of 35 microns, Hoz copper foil corresponds to a copper foil thickness of 18 microns, and so on.
[0298] 5. Flexural modulus
[0299] The aforementioned copper-free substrate was used to make the test samples (3 inches in length and 1 inch in width), and the bending modulus (in GPa) of each sample was measured using a universal testing machine according to the method of IPC-TM-6502.4.4. A bending modulus difference greater than or equal to 3% indicates that there is a significant difference between different samples (there is a significant technical difficulty).
[0300] By referring to the characteristic test results in Tables 1 to 5, the following phenomena can be clearly observed.
[0301] From Examples E1 to E15, it can be determined that the resin composition and its products of the present invention can be improved in one or more or all of the properties such as thermal decomposition temperature, Z-axis thermal expansion coefficient, reflow soldering shrinkage ratio, interconnection structure reliability and bending modulus.
[0302] Embodiments E1 to E3 and E14 contain saturated compounds of formula (2), specifically compounds of formula (2-1), compounds of formula (2-2) or compounds of formula (2-3). Embodiments E4 to E13 and E15 contain unsaturated compounds of formula (2), specifically compounds of formula (2-4), compounds of formula (2-5) and compounds of formula (2-6) or a combination of two or more thereof. From the test results, it can be found that the resin composition containing the unsaturated compound of formula (2) and its products have achieved more significant improvement in the property of thermal expansion coefficient in the Z axis compared with the resin composition containing the saturated compound of formula (2) and its products.
[0303] The compounds of formula (1) in Examples E1 to E6 and E10 to E14 do not contain o-vinylphenoxy groups, while the compounds of formula (1) in Examples E7 to E9 and E15 contain o-vinylphenoxy groups. The resin composition of the compound of formula (1) containing o-vinylphenoxy groups and its products have achieved more significant improvement in at least the reflow soldering expansion and contraction rate compared to the resin composition of the compound of formula (1) not containing o-vinylphenoxy groups and its products.
[0304] By comparing Examples E1 to E15 and Comparative Examples C1 to C2, it can be found that compared with 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, if the content of the compound of formula (1) is not within the range of 10 to 100 parts by weight, the corresponding resin composition and its products are significantly inferior in at least the reflow soldering shrinkage rate, interconnection structure reliability and bending modulus.
[0305] By comparing Examples E1 to E15 and Comparative Examples C3 to C4, it can be found that compared with 100 parts by weight of the polyphenylene ether resin containing unsaturated carbon-carbon double bonds, if the content of the compound of formula (2) is not in the range of 3 to 20 parts by weight, the corresponding resin composition and its products are significantly inferior in at least the Z-axis thermal expansion coefficient, reflow soldering shrinkage ratio, interconnection structure reliability and bending modulus.
[0306] By comparing Examples E1 to E15 and Comparative Examples C5 to C7, it can be found that if a conventional hardening accelerator different from the compound of formula (2) is used, the corresponding resin composition and its products are significantly inferior in at least the Z-axis thermal expansion coefficient, reflow soldering shrinkage ratio, interconnection structure reliability and bending modulus.
[0307] By comparing Examples E1 to E15 and Comparative Examples C8 to C9, it can be found that if a conventional flame retardant different from the compound of formula (1) is used, the corresponding resin composition and its products are significantly inferior in at least the thermal decomposition temperature, Z-axis thermal expansion coefficient, reflow soldering shrinkage ratio, interconnection structure reliability and bending modulus.
[0308] The above implementation modes and examples are essentially only for auxiliary explanation and are not intended to limit the embodiments of the present invention or the application or use of these embodiments. In the present invention, a term similar to "example" means "as an example, example or illustration". Any exemplary implementation form herein is not necessarily interpreted as being preferred or more advantageous than other implementation forms, unless otherwise specified.
[0309] In addition, although at least one exemplary embodiment or comparative example has been proposed in the aforementioned embodiment, it should be understood that the present invention can still have a large number of variations. It should also be understood that the embodiments herein are not intended to limit the scope, use or configuration of the requested technical solution in any way. On the contrary, the aforementioned embodiment can provide a simple guide for those skilled in the art to implement one or more of the aforementioned embodiments and their equivalents. In addition, the claims include known equivalents and all foreseeable equivalents when the present patent application is filed.
Claims
1. A resin composition, characterized in that include: (A) 100 parts by weight of a polyphenylene ether resin containing unsaturated carbon-carbon double bonds; (B) 10 to 100 parts by weight of a compound of formula (1); as well as (C) 3 to 20 parts by weight of a compound of formula (2), In formula (1), n is an integer from 3 to 6, X and Y each independently represent an o-vinylphenoxy group, a m-vinylphenoxy group or a p-vinylphenoxy group; In formula (2), each of X', Y' and Z' independently represents an alkyl group having 1 to 4 carbon atoms, a phenyl group, a hydrogen atom or a group containing an unsaturated carbon-carbon double bond.
2. The resin composition according to claim 1, characterized in that The polyphenylene ether resin containing unsaturated carbon-carbon double bonds includes any one of vinylbenzyl polyphenylene ether resin, (meth)acryl polyphenylene ether resin, vinyl polyphenylene ether resin or a combination thereof.
3. The resin composition according to claim 1, characterized in that The compound of formula (1) has at least one o-vinylphenoxy group.
4. The resin composition according to claim 1, characterized in that The compound of formula (2) has at least one group containing an unsaturated carbon-carbon double bond.
5. The resin composition according to claim 1, characterized in that In formula (2), at least one of X', Y' and Z' represents a vinyl group, a styryl group, an allyl group or a (meth)acryloyloxy group.
6. The resin composition according to claim 1, characterized in that The compound of formula (1) includes any one or a combination of compounds of formula (1-1) to compounds of formula (1-14):
7. The resin composition according to claim 1, characterized in that The compound of formula (2) includes any one of the compounds of formula (2-1) to formula (2-6) or a combination thereof:
8. The resin composition according to claim 1, characterized in that The resin composition further comprises 2 to 30 parts by weight of a cross-linking agent containing unsaturated carbon-carbon double bonds, wherein the cross-linking agent containing unsaturated carbon-carbon double bonds is any one of bis(vinylphenyl)ethane, divinylbenzene, divinylnaphthalene, divinylbiphenyl, triallyl isocyanurate, triallyl cyanurate, vinylbenzocyclobutene, di(vinylbenzyl)ether, trivinylcyclohexane, diallyl bisphenol A, difunctional or higher acrylate, butadiene, decadiene, octadiene, or a combination thereof.
9. The resin composition according to claim 1, characterized in that The resin composition further comprises any one of polyolefin, benzoxazine resin, epoxy resin, polyester resin, phenol resin, amine curing agent, polyamide, polyimide, styrene maleic anhydride, cyanate ester or a combination thereof.
10. The resin composition according to claim 1, characterized in that The resin composition further comprises any one of an inorganic filler, a flame retardant different from the compound of formula (1), a hardening accelerator different from the compound of formula (2), an inhibitor, a solvent, a silane coupling agent, a dye, and a toughening agent, or a combination thereof.
11. A product made from the resin composition according to claim 1, characterized in that: Includes prepreg, resin film, laminate or printed circuit board.
12. The product according to claim 11, characterized in that The thermal decomposition temperature measured according to the method of IPC-TM-6502.4.24.6 is greater than or equal to 430°C.
13. The article according to claim 11, characterized in that The Z-axis thermal expansion coefficient measured according to the method of IPC-TM-6502.4.24.5 is less than or equal to 0.89%.
14. The article according to claim 11, characterized in that The Z-axis thermal expansion coefficient measured according to the method of IPC-TM-6502.4.24.5 is less than or equal to 0.75%.
15. The article according to claim 11, characterized in that The reflow shrinkage rate measured according to the method of IPC-TM-6502.4.39 is less than or equal to 270ppm.
16. The article according to claim 11, characterized in that The resistance value change rate after 1000 cycles measured according to the method of IPC-TM-6502.6.26 is less than 10%.
17. The article according to claim 11, characterized in that The flexural modulus thereof measured according to the method of IPC-TM-6502.4.4 is greater than or equal to 22 GPa.
Citation Information
Patent Citations
Curable resin composition
US20070129502A1
Polyphenylene oxide resin, method of preparing polyphenylene oxide resin, polyphenylene oxide prepolymer and resin composition
US20160185904A1